Investigation of Al(TfO)3-based deep eutectic solvent electrolytes for aluminium-ion batteries. Part I: understanding the positively charged Al complex formation. Issue 38 (24th September 2021) - Peters, Willi; Duong, Hong Thu; Lee, Soobin; Drillet, Jean-Francois
Abstract : This experimental study reveals the presence of mainly two-fold positively charged aluminium complexes in NMA : Al(TfO)3  : urea mixtures caused by bidentate hydrogen bonding between Al triflate and urea at a specific 1 : 4 ratio. Abstract : Aluminium-ion batteries (AIB) are very attractive energy storage systems due to the high availability and theoretical energy density of metallic aluminium. However, the practical performance of AIBs in AlCl3 -based electrolytes is limited by the low reversible capacity of the positive graphite electrode for large AlCl4 − anions. Moreover, the use of high energy oxide-based electrodes such as MnO2 requires the presence of positively charged aluminium complexes in the electrolyte. In this work, the coordination of Al complexes in deep eutectic solvents (DESs) composed of Al triflate Al(TfO)3 as the conducting salt, urea and/or acetamide as the hydrogen bond donor and formamide and N -methylacetamide as the solvent was investigated. Both solvents were able to dissolve and dissociate Al(TfO)3 principally to a single positively charged Al complex [Al(TfO)2 –solvent n ] + which was confirmed by Raman and NMR spectroscopy analyses. Furthermore, the addition of urea led to further dissociation to the [AlTfO–solvent n –urea2 ] 2+ complex that can be assigned to the bidentate hydrogen bonding of urea with TfO at a specific ratio of urea/Al(TfO)3 of 4 : 1. Because of their partial miscibility with urea, other conventional solvents such as propylene carbonate and acetonitrile dissociate Al(TfO)3 only once to form [AlTfO2 –solvent n ] + . The as-prepared formamide and N -methylacetamide-based DES electrolytes show good conductivity values of 9.65 and 2.45 mS cm −1, respectively.